Bibliografia Publikacji Pracowników Politechniki Krakowskiej – baza współtworzona przez społeczność uczelni - Kowalska, Aneta; Lipińska, Dorota (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The Bibliography of Employee Publications of the Cracow University of Technology (BPP PK) has been created in the Library of the Cracow University of Technology (BPK) since 1964, initially in printed form, since 1991 in the form of an electronic database. In September 2013, BPP PK was moved to a platform that was created as part of the project implemented by BPK under the name SUW Integrated System for Knowledge Exchange and Access to Academic Publications in the Field of Technical Sciences. The paper discusses the collection of information, communication regarding BPP PK resources, database modifications, data presentation, and use of collected data. The cooperation of librarians and users was presented from the moment of publication of the publication in BPP PK, through participation in the process of verification of the publication's description, to the moment of publishing the data. Also included is information on the possibility of supplementing or correcting data already made public, the possibility of using data from the BPP PK database in the process of parameterization of scientific units and the periodic assessment of researchers. New technical solutions implemented in 2014 in BPP PK, the requirement of database users' participation in its creation, functioning and development, are part of the Library 2.0 model. BPP PK in its currently functioning form is an example of a dynamic work co-created by the PK university community.